Who decides to grow orange sweet potatoes? Bargaining power and adoption of biofortified crops in Uganda. - Gilligan, Daniel O.; Kumar, Neha; McNiven, S.; Meenakshi, J.V.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2014)
The goal of the HarvestPlus reaching end users (REU) orange sweet potato (OSP) project is to increase vitamin A intake and improve vitamin status among Vulnerable populations (women and children) in rural Uganda by introducing beta-carotene-rich OSP, as well as related messages concerning agronomy, nutrition, and marketing. Most households obtain planting material for these crops through interaction with other households. This raises a number of important questions about the roles of social interaction, intrahousehold division of labor, and gender in determining the rates at which these biofortified crops are adopted and spread. As part of the Gender, Agriculture, and Assets Project (GAAP), this study examines the effect of women’s bargaining power, as revealed in gender¬‐based patterns of ownership and control of land and assets, on adoption ofOSP and vitamin A intake among children.